Differences of Confirmatory Case, Mortality Rate and Incident Mortality of COVID-19 in Indonesia, Asia and Who Online Data Case Study (Jurnal Ilmu Kesehatan Masyarakat, 2021)
Turkish Ministry of Health estimated that 6.3% cases of COVID-19 fatality in April 2020 and 2.1% cases of COVID-19 mortality are associated with multi-factors. COVID-19 is very dangerous for moderate respiratory infection and has higher mortality compared to other diseases such as SARS-CoV-2. The study aims to compare case confirmation, mortality and compare incidence rate mortality between Indonesia and the world’s general situation. The study designs used a cross-sectional study with secondary data. The study population was people who have been diagnosed to covid-19 based on the website with URL: https://covid19.who.int/ and URL: https://covid19.kemkes.go.id/ for the period of March 2020 to November 2020. The Independent Variables are areas of disease i.e. Indonesia, Asia, and world area. Statistical analysis was performed using SPSS. Data were analyzed with ANOVA. Average of confirmatory covid-19 is 1891.65±1468.412 in Indonesia, 41146.94±34159.12 in Asia, and 211914.42±128689.95 according to WHO. The average mortality was 62.29±37.69 in Indonesia, 635.36±453.68 in Asia, and 5279.71±1540.41 according to WHO. The incidence mortality rate was 0.046±0.0326 in Indonesia, averaged 0.023±0.0157 in Asia, and averaged 0.035±0.0231 according to WHO. There was a significant difference in confirmatory case between Indonesia, Asia and WHO with p<0.001, a significant difference in mortality between Indonesia, Asia and WHO with p<0.001, and significant difference in incidence mortality between Indonesia, Asia, and Indonesia with p<0.001. The study was concluded that there are significant differences in confirmatory case, death, and incident mortality between Indonesia, Asia and WHO. Confirmatory case and mortality were higher in WHO and Asia when compared to Indonesia, but incidence mortality was high in Indonesia when compared to WHO and Asia.